The ichthyofaunistic colonization and complex biogeographic history of the southern portion of the Southwest Atlantic Ocean - Figueroa, Daniel Enrique (2023)
Here, we highlight the geological processes that resulted in the current conformation of the southern Southwest Atlantic Ocean, and explore the heterogeneous composition of the marine ichthyofauna found between 33° and 56° from a paleobiological perspective. During the early Cretaceous (140 Mya), the South Atlantic was still not formed, and Gondwana was probably a set of united plates with shallow continental waters. In the middle Cretaceous (112 Mya), the major Gondwanan plates started diverging from each other, allowing shallow marine intrusions and the diversification of an endemic fish fauna. By the end of the Mesozoic (66 Mya), the proto-South Atlantic connected with the North Atlantic, which was still part of the Tethys Sea, allowing its ichthyofauna to colonize the south and reach the Antarctic region. The opening of the Drake Passage in the Oligocene (33 Mya) enabled the cold waters of the Pacific Ocean to reach the South Atlantic, causing drastic effects on the thermophilic fauna and favoring the dispersion of cold-water species. Successive glaciations during the Quaternary (2 Myr to 10,000 years ago) resulted in the prevalence of Antarctic climatic conditions in the southern Southwest Atlantic. The long history of changing scenarios in the constitution of the southern Southwest Atlantic is reflected in the heterogeneous composition of the marine ichthyofauna between 33° and 56°S, which is characterized by a mixture of cosmopolitan, Tethyan, Pacific, Gondwanan, Antarctic, and endemic origins.